Concepts in marketing - Coast Learning Systems ([Fountain Valley, CA] : Coast Learning Systems, 2004)
Provides a comprehensive survey of fundamental marketing principles and skills. Students will learn how marketing managers develop strategy, research consumer needs, and identify target markets
Introduction to marketing (27 min.) -- Marketing strategy (27 min.) -- Environmental scanning (27 min.) -- Ethics and social responsibility (27 min.) -- Consumer behavior (27 min.) -- Marketing research (27 min.) -- Segmenting and targeting markets (27 min.) -- Managing products and services (27 min.) -- Pricing products and services (27 min.) -- Marketing channels and supply chains (27 min.) -- Retailing and wholesaling (27 min.) -- Integrated marketing communications (27 min.) -- Advertising, sales promotion, and public relations (27 min.) -- Personal selling and sales management (27 min.) -- Interactive and multichannel marketing (27 min.)
Title from container
Keywords: Marketing; Marketing -- Moral and ethical aspects; Marketing research; Marketing channels; Selling; Advertising; Market segmentation